Transcutaneous Sacral Electrical Stimulation for Chronic Functional Constipation. Issue 2 (February 2016) - Iqbal, Fareed; Thomas, Gregory P.; Tan, Emile; Askari, Alan; Dastur, Jamasp K.; Nicholls, John; Vaizey, Carolynne J.
Abstract : BACKGROUND: Transcutaneous sacral nerve stimulation is reported to improve symptoms of fecal incontinence. Chronic constipation may also respond to stimulation, but this is poorly reported in the literature. OBJECTIVE: The study assessed the efficacy of transcutaneous electrical stimulation directly over the sacral nerve roots in chronic constipation. PATIENTS: Chronic functional constipation was established in all patients using the Rome III criteria. SETTING: The therapy was self-administered at home. DESIGN/INTERVENTION: A pilot study was conducted of transcutaneous sacral stimulation given over a 4-week period for 12 hours a day. MAIN OUTCOME MEASURES: Patients were assessed using the Patient Assessment of Constipation Symptoms, the Patient Assessment of Constipation Quality of Life, and the Cleveland constipation tool. A Global Rating of Change measure and a 1-week bowel diary was kept for the final week and compared with baseline. RESULTS: Of the 20 patients recruited (16 female, median age 38.5 years), 80% (16) completed the trial. Five (31%) patients reported at least a point reduction in the Patient Assessment of Constipation Symptoms score, 4 (25%) deteriorated, and 7 (44%) improved by less than one point. Median (interquartile range) Patient Assessment of Constipation Symptoms scores were 2.33 (2.34) at baseline and 2.08 (2.58) at follow-up ( p = 0.074). Median scores for the Patient Assessment of Constipation Quality of Life and Cleveland systems were 3.00 (1.64) and 17.15 (18) at baseline and 2.22 (3.04) and 15.31 (12) at follow-up ( p = 0.096 and 0.111). One-third of patients reported a positive Global Rating of Change measure, although 68% required concurrent laxatives during the trial. LIMITATIONS: This is a pilot study and is limited by its small sample size. CONCLUSIONS: Continuous transcutaneous sacral stimulation in the short term appears to be ineffective for chronic constipation. Larger well-powered studies with intermittent stimulation regimens are required to investigate this further.